1996
DOI: 10.1017/s0952523800007744
|View full text |Cite
|
Sign up to set email alerts
|

The number and distribution of bipolar to ganglion cell synapses in the inner plexiform layer of the anuran retina

Abstract: The main route of information flow through the vertebrate retina is from the photoreceptors towards the ganglion cells whose axons form the optic nerve. Bipolar cells of the frog have been so far reported to contact mostly amacrine cells and the majority of input to ganglion cells comes from the amacrines. In this study, ganglion cells of frogs from two species (Bufo marinus, Xenopus laevis) were filled retrogradely with horseradish peroxidase. After visualization of the tracer, light-microscopic cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Stated another way, ganglion cells are more likely to be a third‐order neuron with GABAergic bipolar cells, whereas they are more likely to be a fourth‐order neuron with glutamatergic bipolar cells. Buzas et al (1996) reported that only 10–20% of the ribbon dyads in Bufo and Xenopus make direct contact with ganglion cells. This amount is a much smaller proportion compared with that reported for bipolar cells in retinas of urodele amphibians (Dowling and Werblin, 1969; Wong‐Riley, 1974; this report).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stated another way, ganglion cells are more likely to be a third‐order neuron with GABAergic bipolar cells, whereas they are more likely to be a fourth‐order neuron with glutamatergic bipolar cells. Buzas et al (1996) reported that only 10–20% of the ribbon dyads in Bufo and Xenopus make direct contact with ganglion cells. This amount is a much smaller proportion compared with that reported for bipolar cells in retinas of urodele amphibians (Dowling and Werblin, 1969; Wong‐Riley, 1974; this report).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that bipolar cells make ribbon synapses and amacrine cells make conventional synapses onto target cells in all vertebrate retinas so far studied (Kidd, 1962; Dowling and Boycott, 1966; Raviola and Raviola, 1967; Dowling, 1968; Dowling and Werblin, 1969; Witkovsky and Dowling, 1969; Dubin, 1970; Goldman and Fisher, 1978; Gabriel and Straznicky, 1993; Buzas et al, 1996). Despite a casual description of non‐ribbon synapses of bipolar cells in human retina by Allen (1969), the first extensive documentation of these synapses was made by Wong‐Riley in 1974 in tiger salamander retina, a finding later confirmed by Yang and Wang (1999) and Miller et al (2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In frogs, the bipolar cells are mixed, receiving inputs from both rods and cones (Dowling, 1968;. In the IPL, in about 70% of the cases both of the postsynaptic profiles at a ribbon synapse derived from amacrine cells (Buzá s et al, 1996;Gá briel and Wilhelm, 1994;Goldman and Fisher, 1978;Zhu and Gibbins, 1997). This observation suggests a higher divergence of bipolar cell output to amacrine cells in frogs than in mammals.…”
Section: Bipolar To Amacrine Cell Contactsmentioning
confidence: 99%
“…In recent years, evidence has accumulated that retinal ganglion cells in anurans receive a sizable direct input from BCs (Buzás et al 1996;Zhu and Gibbins 1997). However, we still do not know if all ganglion cell types receive equal amounts of direct BC inputs or not.…”
Section: Convergence Divergence and Acuitymentioning
confidence: 97%